Outlook for Remittance Flows 2011-13 : Remittance Flows Recover to pre-Crisis Levels - Mohapatra, Sanket (World Bank, Washington, DC, 2012)
Officially recorded remittance flows to developing countries recovered quickly to $325 billion in 2010 after the global financial crisis. But they have not kept pace with rising prices in recipient countries. Remittance flows are expected to grow at lower but more sustainable rates of 7-8 percent annually during 2011-13 to reach $404 billion by 2013. Remittance flows to Latin America are growing again in 2011 because of the stabilization of the U.S. economy. Remittance flows from Russia and the Gulf Cooperation Council (GCC) countries to Asia have been strong due to high oil prices. However, weak job markets in Western Europe are creating pressures to reduce migration. The crisis in the Middle East and North Africa has brought a great deal of uncertainty for migration and remittance flows. These political crises and the recent global financial crisis have highlighted, once again, the need for high-frequency data on migration and remittances.